2016
DOI: 10.1080/03007995.2016.1232706
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive treatment and blood pressure control in patients with hypertension in daily clinical practice: a cross-sectional, multicenter, observational study in Egypt

Abstract: The majority of patients from Egypt had uncontrolled hypertension even after receiving treatment. This might increase awareness among physicians and enable them to prescribe appropriate treatment to patients with uncontrolled BP. Key limitations: The questionnaire used in the study for the evaluation of patient/physician satisfaction level was not standardized and was based on the choice and practice of the physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In addition, strong associations have been reported between OSA and the prevalence of hypertension (HTN) independently of other CV risk factors [15]. Further, a recent cross-sectional study conducted on around 4000 Egyptian patients with HTN found that 63% of the cohort had uncontrolled blood pressure values despite treatment, and about half of those patients had an increased BMI [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, strong associations have been reported between OSA and the prevalence of hypertension (HTN) independently of other CV risk factors [15]. Further, a recent cross-sectional study conducted on around 4000 Egyptian patients with HTN found that 63% of the cohort had uncontrolled blood pressure values despite treatment, and about half of those patients had an increased BMI [16].…”
Section: Introductionmentioning
confidence: 99%
“…, 48. , 49 Other studies were conducted in Japan (n = 2), 25 , 26 Nigeria (n = 2), 14 , 15 Saudi Arabia (n = 2), 19 , 50 Egypt (n = 1), 22 Jordan (n = 1), 51 Pakistan (n = 1), 24 Bahrain (n = 1), 16 Kenya (n = 1), 27 Australia (n = 1), 34 Cyprus (n = 1), 35 Ireland (n = 1), 52 United Arab Emirates (n = 1), 18 Taiwan (n = 1), 53 and Mexico (n = 1). 17 …”
Section: Resultsmentioning
confidence: 99%
“…, 33 , 36 , 39 , 42 , 50 , 53 while 10 studies were conducted in outpatient clinics. 14 , 22 , 27. , 28 , 29 , 40 , 41 , 47 , 48 , 51 Six studies were based on national prescribing databases, 26 , 34 , 38 , 44 , 45 , 52 and four studies were conducted in primary care centers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two studies found a significant association between poor blood pressure control and diabetes. 10,21…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two studies found a significant association between poor blood pressure control and diabetes. 10,21 A quality assessment of the included studies assessed by using NOS checklist indicated that 18% (n = 5) were of poor quality, 37.0% (n = 10) were fair, and 44.0% (n = 12) were of good quality.…”
Section: Use Of Antihypertensive Agentsmentioning
confidence: 99%